Root Canal Morphology of Human Mandibular First Permanent Molars in an Iranian Population - Saeed Rahimi; Hamid Reza Yavari; Shahriar Shahi; Reza Torkamani (Tabriz University of Medical Sciences, 2008)
Background and aims. The knowledge of variations in root canal morphology is critical for a successful endodontic treatment. The purpose of this study was to investigate variations in the root canal system of human mandibular first permanent molars in an Iranian population. Materials and methods. In this study, 209 mandibular first molar teeth were decalcified, dye-injected, and cleared in order to determine the number and configuration of the root canals. Results. The results demonstrated that 65.56% of the mandibular first molars under study had three, 31.57% had four and 2.87% had two canals. Conclusion. According to the results of this study and considering variations in the root canal systems of the mandibular first molars, it seems that great care should be taken in the root canal treatment of these teeth.